2009
DOI: 10.1111/j.1365-2966.2009.14920.x
|View full text |Cite
|
Sign up to set email alerts
|

The first outburst of the new magnetar candidate SGR 0501+4516

Abstract: We report here on the outburst onset and evolution of the new soft gamma‐ray repeater SGR 0501+4516. We monitored the new SGR with XMM–Newton starting on 2008 August 23, 1 day after the source became burst active, and continuing with four more observations in the following month, with the last one on 2008 September 30. Combining the data with the Swift X‐ray telescope (Swift–XRT) and Suzaku data, we modelled the outburst decay over a 3‐month period, and we found that the source flux decreased exponentially wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
126
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 76 publications
(103 reference statements)
14
126
0
Order By: Relevance
“…The unabsorbed 0.5-10 keV flux data points are from XMMNewton observations. The first five data points are taken from Rea et al (2009) and the sixth data point is taken from Camero et al (2014). The X-ray luminosity is calculated assuming a distance of 5 kpc.…”
Section: X-ray Outburst Of Sgr 0501+4516mentioning
confidence: 99%
See 2 more Smart Citations
“…The unabsorbed 0.5-10 keV flux data points are from XMMNewton observations. The first five data points are taken from Rea et al (2009) and the sixth data point is taken from Camero et al (2014). The X-ray luminosity is calculated assuming a distance of 5 kpc.…”
Section: X-ray Outburst Of Sgr 0501+4516mentioning
confidence: 99%
“…For NH = 10 22 cm −2 (Rea et al 2009) we have converted the observed magnitudes when the X-ray luminosity is close to the quiescent level [i = 24.4 ± 0.4, u > 24.7, g > 26.9, K = 19.7 ± 0.1 (Dhillon et al 2011)] into the unabsorbed flux values. It is seen in Fig.…”
Section: Long-term Evolution Of Sgr 0501+4516mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, six other faint X-ray sources underwent similar outbursts (X-ray flux variation of a factor ∼100). These sources were consequently classified as transient magnetars: 1E 1547.0-5408, CXOU J164710.2−455216, SGR 1627-41, SGR 0501+4516, 1E 1547.0-5408, SGR 0418+5729, and SGR 1833−0832 (Muno et al 2007;Israel et al 2007;Esposito et al 2008;Rea et al 2009;van der Horst et al 2010;Gögüş et al 2010;Esposito et al 2010). This suggested that presently known sources constitute only a fraction of a much larger, still undetected, magnetar population.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, only a handful of short bursts were imaged by SA, originating in SGR 1806-20, 1E 1547.0-5408, and SGR 0501+4516. The latter was indeed monitored during a dedicated target of opportunity observation approximately 10 days after its discovery, from 31st August to 10th September, but the source turned out to have gone back to an almost burst-quiescent state (see, e.g., Rea et al 2009) and only 2 short bursts were detected by SuperAGILE ). Examples of short bursts from the SGR sources detected by SA are shown in Fig.…”
Section: Galactic Transientsmentioning
confidence: 99%